AB1340 Differential characteristics in a cohort of colombian patients with three autoimmune/autoinflammatory diseases: a national registry under a risk management model. (12th June 2018) - Pineda-Tamayo, R.; Diaz-Coronado, J.C.; Hernandez Parra, D.; Perez-Estrada, P.; Salazar-Uribe, J.C.; Alzate, M.-A.; Rojas-Villarraga, A.
Abstract : Background: Latin American (LA) population with autoimmune/autoinflammatory (AID/AI) diseases is considered as a minority, with special characteristics of ancestry, socioeconomic status (SES) and cultural among others, with particular manifestations and prognosis outcomes Objectives: To describe the largest cohort of patients with rheumatoid arthritis (RA), spondyloarthropathies (SpA) and systemic lupus erythematosus (SLE), in Colombia, evaluated through the social health care security system (SHCSS) and under a risk management model highlighting shared characteristics, as well as differences Methods: A national register-based retrospective cohort study of the SHCSS since 2015 assessing three AID/AI diseases (RA, SLE, SpA) treated in a centre of excellence in rheumatology, under a risk management program in six cities of Colombia. Data about covered population was obtained from the integral information system of SHCSS (SISPRO). Clinical records of patients with AID/AI ICD-10 codes were selected. Adult patients fulfilling international validated diagnoses criteria for the three AID/AI were included. A survey data collection instrument was implemented. Analyses (SAS software V9.4) with standard statistical methods (Polytomous logistic regression, Chi-squared test Fisher's exact test, and Kruskal-Walis test) were done. Odds ratio (OR) and 95% percent CIs were computed (p<0.05) Results: Of 1 62 487 population covered from national security system (SISPRO data) having AID/AI diseases, 71 515 were evaluated in the 6 cities and 12 323 records were selected of patients by population census attended in the institution. A total of 5372 records meet international validated criteria and were included (RA=3576, SLE=1175, SpA=621). RA patients were older, had lower educational level and SES, longer duration of the disease and late age at onset. Cardiovascular compromise was high in RA and SLE. Polyautoimmunity was predominant in SLE. A total of 89% of patients were under steroids treatment (SLE and RA) and 35% in SpA. Biologics were indicated in 59% (SpA), 23% (RA) and 7, 1% (SLE). EuroQol five dimensions scores were significantly better in the SLE group (time of admission). Additional clinical characteristics are described in Table 1 Conclusions: This is the largest cohort evaluated through the SHCSS and under a risk management model in Colombia (LA). This population share special characteristics, highlighting differences between these three AID/AI diseases that are frequently evaluated in the same scenario in real life conditions by the rheumatologist. It is worth noting the specific poor prognosis factors of RA and the high percentage of patients under biological treatment in SpA group, which implies a high cost for the health system Reference: [1] O. Valencia, P. Sánchez, L. Acuña, et al. Ann Rheum Dis2017;76 supplement:1536 Disclosure of Interest: None declared